Wide-angle mechanical scanning Transmit-arrays for satellite Ka-band user terminals - Matos, S.; Costa, J. R.; E. B. Lima; Parinaz Naseri; C. A. Fernandes; Fonseca, N. J. G. (2018 IEEE International Symposium on Antennas and Propagation and USNC-URSI Radio Science Meeting, 2018)
The antenna design for broadband satellite communications is particularly challenging, new cost-effective solutions are still needed. An overview of recent contributions from the authors on planar transmit-arrays (TAs) for satellite Kaband user terminals is presented. We tackle several design problems: how to improve the scanning coverage using low cost mechanical beam steering, how to choose the type of unit cells that compose the TA, how to devise a single aperture with high gain that operates simultaneous at two widely separate frequency bands. Different prototypes are used to conduct these studies. All these TAs provide wide beam zenith scanning, [-50º,50º] with less that 3dB of scan loss, good circular polarization performance and low beam distortions. The prototypes have the same aperture size, 195 × 145 mm2, that provide gains up to 29 dBi for 30 GHz.